The High Impact of Staphylococcus aureus Biofilm Culture Medium on In Vitro Outcomes of Antimicrobial Activity of Wound Antiseptics and Antibiotic - Justyna Paleczny; Adam Junka; Malwina Brożyna; Karolina Dydak; Monika Oleksy-Wawrzyniak; Daria Ciecholewska-Juśko; Ewelina Dziedzic; Marzenna Bartoszewicz (Pathogens, 2021)
The staphylococcal biofilm-based infections of wounds still pose a significant therapeutical challenge. Treated improperly, they increase the risk of limb amputation or even death of the patient. The present algorithms of infected wound treatment include, among others, the application of antiseptic substances. In vitro wound biofilm models are applied in order to scrutinize their activity. In the present work, using a spectrum of techniques, we showed how the change of a single variable (medium composition) in the standard in vitro model translates not only to shift in staphylococcal biofilm features but also to the change of efficacy of clinically applied wound antimicrobials such as octenidine, polyhexamethylene biguanide, chlorhexidine, hypochlorite solutions, and locally applied gentamycin. The data presented in this study may be of a pivotal nature, taking into consideration the fact that results of in vitro analyses are frequently used to propagate application of specific antimicrobials in hospitals and ambulatory care units.